Membangun Masa Depan Berkelanjutan: Kebutuhan Gender, Pendidikan, dan Tenaga Kerja Generasi Z di Negara Jepang, Korea Selatan dan Indonesia - Indriyani, Nina; Nurjanah, Nunung; Widiyanti, Widiyanti; Effendi, Muhammad Idris (Vocational College of Diponegoro University, 2025)
This study aims to explore the interconnection between gender equality, education, and the workforce of Generation Z in Japan, South Korea, and Indonesia, focusing on their roles in sustainable development. With rapid technological advancement and globalization, Generation Z is expected to be the primary driver of future labor markets. However, challenges related to gender inequality, education gaps, and labor market readiness persist in these countries. This paper reviews recent literature to identify existing research gaps, particularly the lack of comprehensive studies integrating gender equality, education, and workforce development within the framework of sustainable development. Previous studies have focused on individual aspects, but there is limited research that holistically examines these factors across multiple countries with differing socio-economic contexts. By employing a qualitative approach, this study analyzes secondary data, government reports, and interviews with experts to examine how gender equality, educational access, and workforce preparedness can contribute to the achievement of sustainable development goals in these three nations. The research hypothesis suggests that inclusive education and stronger gender equality policies will improve the workforce readiness of Generation Z, ultimately accelerating sustainable development in Japan, South Korea, and Indonesia. The findings of this study aim to provide actionable policy recommendations to promote gender equity, educational inclusivity, and labor market readiness, thereby enhancing the long-term sustainability of these countries.